A study on common sexually transmitted disease infection in infertile female attended to infertility clinic, HUSM, Kota Bharu, Kelantan. - Hussain, Nik Hazlina Nik; Lah, Nik Ahmad Zuky Nik (2004)
Introduction: Sexually tramsmittcd disease (STDs), once call ed venereal disease, are among the most common infectious diseases in the world. In Western countries, there has been a dramatic increase in the reported incidence 0f sexually transmitted diseases (STD) during the past 25 years. It is tragic irony that despite medical efforts against sexually transmitted di seases and the existence, since the 1 9~0 s, of powerrul treatments for them, !he~e di se~ses ~,,crs ist; eVC:il il11 ive in the twenty first century. This trend was augmented by ea rlier sexual maturity in girls and earlier age of onset of sexual activity in both sexes. Other sociological changes which contribute to the increased incidence of STD include urbani7.ation, increased mobility among the young, and the greater ease of world-wide tra vel. Sexual tourism is increasingly common. This last factor has also promoted the importation of unusual tropical STDs and antibioticresistant infections. Traditionally, five diseases ha ve been class ified as sexually transmitted diseases which are syphilis, gonorrhoea, lyphogranuloma venereum, chancroid, and granuloma inguinale. Lyphogranuloma venereum is one of disease caused by Chlamydia thrachomatis. To d~t e more than 20 distinct sex ually transmitted or transmissible pathogens were identified which may have different clinical lllanifestations. Ilowever in this study we are only concentrate on three common sexually tran smitted diseases which are chlamydia! infection, gonorrhoea and syphilis. Chlamydia! inti!ction and gonorrhoea are wdl known to cause pelvic inflammatory disease (PID) and their sequelae; infertility, chronic pehic pain and ectopic pregnancy, whereas syphilis affect the outco1ne of the baby before and after the pregnancy. Another important issue is that, the genital chlarnydial int'tction is mcreasing in trend worldwide. Objectives: To determine the local prevalence of common organism m Sexually Traus1niued Diseases (STDs) infections (C 'hlun~vdia lracbrnuatis, gonorrhoea and syphilis) in intertHe len1ales attended to Jntertihty Clinic Hospital Universiti Sains Malaysia, Kubang Kerian, Kota Bhant, Kelantau. And to dctennine the clearance rate of ('h/anzydia trachoJJzalis and gonorrhoea infection after a course of azithromycin I gram single dosage. Methodology: This 1s a prospective study involving 150 intertile females under fOllow up at infertility clinic Department of Obstetrics and Gynaecology, Hospital Universiti Sa ins tvtalaysia between I st of March 2002 lill 281h of February 2003 . Endocervical saruples were obtained to detect ( 'hla11~~·dia trachotnatis by direct immunofluorescence, Nei.1·seria gonorrhoea by Gram smear and culture & sensitivity. Blood sa1nples vverc also obtained tbr Venereal Disease Research Laboratory (VDRL) testing and tor lg f\·1 antibody toward chla1nydia. For VORL testing positive patient another blood san1plc tor 'lieponetna pallidun Conclusion: The prevalence of sexually transtnitted diseases (Chlarnydia trachomatis, gonorrhoea and syphilis) infection in infertile female is lo\v in our studied g~oup. The 8 clearance rate of Chlanzydia trachrnnatis infection by azithrotnycin is good. There is statistically significant correlation behveen the incidences of tubal factor causing infertility \vith Chlamydia trachontatis infection arnong thern. The prevalence is not a true representation of Malaysian populations as it is a hospital-based study. A larger scale study involving a few centers i~ needed in order to obtain a better representation of Malaysian populations.